2023
DOI: 10.1002/osp4.692
|View full text |Cite
|
Sign up to set email alerts
|

Higher body mass index is strongly linked to poor outcomes in adult COVID‐19 hospitalizations: A National Inpatient Sample Study

Abstract: AimsThe coronavirus disease 2019 (COVID‐19) pandemic has resulted in more than six million deaths worldwide. Studies on the impact of obesity on patients hospitalized with COVID‐19 pneumonia have been conflicting, with some studies describing worse outcomes in patients with obesity, while other studies reporting no difference in outcomes. Previous studies on obesity and critical illness have described improved outcomes in patients with obesity, termed the “obesity paradox”. The study assessed the impact of obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…This statement still holds true even in the post-COVID-19 pandemic era as different hospitals have different nutritional practices, especially tube feeding and parenteral nutrition, which makes it beneficial to be slightly overweight. Elkhapery et al (2024) showed no significant mortality difference among overweight patients with a BMI of 25 to <30 infected with COVID-19, while a higher BMI was linked to higher mortality [26]. Lastly, we did not perform any statistical analysis on baseline laboratory values; nonetheless, patients receiving SOC plus either of the study agents had numerically higher laboratory values than those treated only with SOC.…”
Section: Discussionmentioning
confidence: 80%
“…This statement still holds true even in the post-COVID-19 pandemic era as different hospitals have different nutritional practices, especially tube feeding and parenteral nutrition, which makes it beneficial to be slightly overweight. Elkhapery et al (2024) showed no significant mortality difference among overweight patients with a BMI of 25 to <30 infected with COVID-19, while a higher BMI was linked to higher mortality [26]. Lastly, we did not perform any statistical analysis on baseline laboratory values; nonetheless, patients receiving SOC plus either of the study agents had numerically higher laboratory values than those treated only with SOC.…”
Section: Discussionmentioning
confidence: 80%